Prefaciais (Revista de Educação Pública, 2012)
Conselho EditorialBernardete A. GATTIFundação Carlos Chagas – São Paulo/SPCelso de Ruy BEISIEGELUSP – São Paulo/SPChristian ANGLADEUniversity of Essex - InglaterraFlorestan FERNANDES(in memorian)Francisco Fernández BUEYUniversitat Pompeu Fabra – EspanhaJean HÉBETTEUFPA – Belém/PAMaria de Lourdes BANDEIRA UFMTCuiabá/MTMartin COYUniv. Tubingen – AlemanhaMoacir GADOTTIUSP – São Paulo/SPNicanor Palhares SÁUFMT – Cuiabá/MTPaolo NOSELLAUFSCar – São Paulo/SPPaulo SPELLERUFMT- Cuiabá/MTWalter E. GARCIACNPq – Brasília/DF